Pengaruh Penggunaan Metode Resitasi Terhadap Keaktifan Belajar Siswa Dalam Pembelajaran Pendidikan Agama Kristen Dan Budi Pekerti Kelas XI SMA Negeri 1 Ronggurnihuta Kabupaten Samosir Tahun Pembelajaran 2023/2024 - Gresi Christina Batubara; Adiani Hulu; Baginda Sitompul; Betty A.S Pakpahan; Robert K.A Simangunsong (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
The aim of this research is to determine the positive and significant influence of the use of the Recitation method on students' active learning in teaching Christian Religious Education and Character in class The research method used is a quantitative research method. The population of all class Data was collected using a positive closed questionnaire with 30 items, namely 15 items for variable SMA Negeri 1 Ronggurnihuta Samosir Regency Academic Year 2023/2024: 1) Data processing results: a) positive relationship test obtained rxy = 0.476 > rtable(=0.05,n=52) = 0.297. b) Testing a significant relationship obtained a value of tcount= 3.827 > ttable(=0.05, dk=n-2=50)= 2.000. 2) Influence test: a) Regression equation test, obtained the regression equation Y ̂=